Vitamin D Deficiency and Insufficiency According to the Current Criteria for Children: Vitamin D Status of Elementary School Children in Turkey - F. Sinem Hocaoğlu-Emre; Devrim Sarıbal; Osman Oğuz (Galenos Yayincilik, 2019)
Objective:This study aimed to determine the ratio of seasonal vitamin D deficiency and insufficiency in elementary school children aged between 6-9 years old, living in one of the largest metropols of Europe, İstanbul.Methods:Serum 25(OH)D levels of 640 children aged 6-9 years old were scanned retrospectively from the hospital information system records between September 2017-August 2018 period. Vitamin D deficiency was defined as a serum 25(OH)D level less than 12 ng/mL (30 nmol/L) and insufficiency as levels between 12 and 20 ng/mL (30-50 nmol/L).Results:Serum 25(OH)D levels ranged from 3.90 to 64.60 ng/mL, the median value was 25.95 ng/mL for all subjects. Of all the primary school children, 485 (75.78%) had adequate levels of 25(OH)D. Vitamin D deficiency was observed in 36 of children (5.62%), whereas insufficient levels of 25(OH)D were found in 119 children (18.60%). The ratio of vitamin D insufficiency and deficiency together was highest in spring (31.87%) and lowest in summer (13.12%).Conclusion:Vitamin D deficiency is a widely observed and preventable public health problem among children of different ages. It is necessary to increase the awareness among health professionals, and providing 25(OH)D supplements will yield generations with healthy bone structure and well growth.